Living in precarious partnerships: Understanding how young men’s and women’s economic precariousness contribute to outcomes of first cohabitation - Palumbo, Lydia; Berrington, Ann; Eibich, Peter (Taylor and Francis, 2025)
In the UK, cohabitation has become the normative type of first co-residential partnership. While some couples go on to marry, others increasingly continue to cohabit or break up. One possible explanation is the rise in young people’s economic precariousness. However, few studies have analysed this hypothesis empirically for the UK. By analysing data on cohabiting couple dyads from 1991 to 2019, we explore how economic precariousness (measured by four traits: employment, labour income, savings, and financial perceptions) relates to marriage and to cohabitation dissolution. The types of precarious traits seen in couples, alongside their distribution between partners, are crucial for understanding socio-economic differences in cohabitation outcomes. Marriage is less likely among couples where the man is jobless or has no savings, suggesting that marriage is a financially committed relationship, more reliant on men’s resources. Couples where women hold worse financial perceptions than men are most likely to separate, highlighting the importance of subjective measures.